The ways to new : 15 paths to disruptive innovation - Dru, Jean-Marie (John Wiley & Sons, Inc., 2015)
Break free and lead the market with the roadmap to Disruption The Ways to New gives you a blueprint for innovation, helping you dig your organization out of the quicksand and get on the fast track to growth. Author Jean-Marie Dru is the originator the Disruption methodology, which he shares here; he is also an international authority on breaking the mold and leading the market, and this book is his guide to making it happen. Too many companies are too slow with innovation. They lag behind, creating at a snail's pace, and thus miss out on any kind of organic growth. They approach new ideas too conservatively, and focus innovation on products only--when there is a whole world out there waiting to be disrupted. This book shows you how to steer your organization toward continued innovation, creation, growth, and success, with 15 proven paths to disruption. Each is illustrated with case studies from companies like L'oreal, Procter & Gamble, and Salesforce.com, to show you the glaring differences between disruption and stagnation. We like to think that we live in a world where innovation happens at a staggering pace. The reality is that we don't, but that leaves an opening that your organization can fill if you're willing to break from the herd. This book shows you how start turning in a new direction, toward sustained, forward-thinking growth. Foster organic growth within your organization Become more proactive about innovation Understand the famous "Disruption" methodology Learn the specific, proven paths to disruption Everyone loves to cite Apple, Google, and Amazon as proof of high-speed innovation. But companies like this represent only 20% of companies worldwide--the other 80% are still floundering and failing to move forward. The Ways to New gives you a roadmap to innovation, and the tools to make it work